Pemberdayaan Ibu-Ibu Rumah Tangga Melalui Wirausaha Makanan Kecil Berbahan Dasar Pisang Di Dusun Ketapang Desa Batu Putih Kecamatan Sekotong Kabupaten Lombok Barat - Nurwahidah; Iswan; Suryaningsih; Dhea Chandra Dewi (CV. Multi Kreasi Media, 2025)
The family is the smallest unit in society that is experiencing change. The family, especially housewives, in addition to having an important role in shaping the child's personality, also plays an important role in improving the family's economy. They not only manage the household and take care of the children, but can also contribute financially. This community service was carried out in Ketapang Hamlet, Batu Putih Village, Sekotong District, where housewives and the surrounding community are partners in this activity. The purpose of this community service is so that housewives in Ketapang Hamlet can process banana raw materials into processed snacks and how to package them so that the product looks attractive to be used as a home business. The method used in this service is to provide training in making snacks made from bananas and discussions about the importance of entrepreneurship to help the family economy. The result of this service is that training participants are able to implement the results of the training as provisions so that they can become entrepreneurs and have skills.